Kondycja władzy w świecie postmodernistycznym. Refleksje inspirowane myślą Jeana Baudrillarda (Świat Idei i Polityki, 2008)
Jean Baudrillard was a controversial sociologist and philosopher. He was the author of the theory of simulacra and simulation. He argued in his works the following thesis: "Reality doesn't exist", "The war is a continuation of the absence of politics by other means" (with reference to Clausewitzian formula), "Terrorist attack on the WTC was absolute event". The author of this article tries to find an answer to the question: Where do the categories of power and leadership occure in Baudrillard's philosophy? In the conclusion the author claims that - according to the French philosopher - political leaders are nowadays the same simulation as reality which they live and act in. In the age of mediatization of politics this thesis is daily validated.